Why I am Concerned about the Environment (Hekima Review, 2010)
In 1987, I witnessed a serious disturbance to the quiet and ordinary life of the rural community where I was born. The community went on an all out war with the rainmaker. The community had requested him to make rain so that the farming cycle could begin. But he could not, and could not explain why. So, the women of the community moved into the rainmaker’s homestead and cooked all the food in his barn. The saga developed over three months, and life was never the same since the drought of that year: all the able bodied people could no longer live on farming; they had to find an alternative source of livelihood. Of course, neither the drought nor the disruption of life it occasioned made it into world news headlines. The disturbance was ‘insignificant’ to draw the attention of the media, and nobody would have made money ‘representing’ either party to the conflict in a court of law. But it has got me thinking about the environment for the past twenty years.